The Anxiety of Social Influence - Sobolczyk, Piotr (Praktyka Teoretyczna, 2014)
The paper ostensibly refers to Harold Bloom’s categories of the anxiety of influence. Bloom’s theory is treated as an immanentist one, i.e. text/aesthetics/personality-oriented, which is specific to the period in which the theory was developed. However, at least from the 80s of the XXth century, there occurs a visible change towards sociologization of all the human sciences. The paper appropriates and resignificates Bloom’s categories and intermingles them with the concepts of social psychology in order to enable a description of the condition of writers in the current social context